LOD human representations: a comparative study - MCDONNELL, RACHEL; O'SULLIVAN, CAROL ANN; DOBBYN, SIMON (My University, 2005)
Real-time crowd systems are increasing in popularity and importance. With this comes the need for accurate low level of detail (LOD) human model representations. Currently, the two most commonly used representations for large scale crowds are image based representations and low level geometric meshes. In this paper, we evaluate the effectiveness of the two representations in terms of their appearance and how accurately they convey motion. We show that low resolution geometry is not equivalent to image based representations at replicating the motion of high resolution geometry. We also report the distances from the camera at which impostors and different simplified meshes are perceptually equivalent to high resolution geometry.
PUBLISHED
Keywords: perception; evaluation; impostors; level of detail